Engineering intelligent systems on the knowledge formalization continuum - Baumeister, Joachim; Reutelshoefer, Jochen; Puppe, Frank (Zielona Góra: Uniwersytet Zielonogórski)
In spite of their industrial success, the development of intelligent systems is still a complex and risky task. When buildingintelligent systems, we see that domain knowledge is often present at different levels of formalization?ranging from textdocuments to explicit rules. In this paper, we describe the knowledge formalization continuum as a metaphor to helpdomain specialists during the knowledge acquisition phase.
Keywords: knowledge engineering; knowledge acquisition; semantic wiki